Hydrophobic hydration of amphipathic peptides. - Cheng, Y K (1999)
Biomolecular surfaces and interfaces are commonly found with apolar character. The hydrophobic effect thus plays a crucial role in processes involving association with biomolecular surfaces in the cellular environment. By computer simulation, we compared the hydrogen bonding structures and energetics of the proximal hydration shells of the monomer and dimer from a recent study of an extrinsic membrane peptide, melittin. The two peptides were studied in their amphipathic alpha-helical forms, which possess extended hydrophobic surfaces characterized by different topography. The topography of the peptide-water interface was found to be critical in determining the enthalpic nature of hydrophobic hydration. This topographical dependence has far-reaching implications in the regulation of bioactivities in the presence of amphipathicity. This result also engenders reconsideration of the validity of using free energy parameters that depend solely on the chemical nature of constituent moieties in characterizing hydrophobic hydration of proteins and biomolecules in general.